Evaluation of radically open dialectical behaviour therapy in an adult community mental health team: effectiveness in people with autism spectrum disorders. (June 2021) - Cornwall, Peter L.; Simpson, Susan; Gibbs, Claire; Morfee, Valerie
Abstract : Aims and method: Radically open dialectical behaviour therapy (RO DBT) is a transdiagnostic treatment designed to address disorders associated with overcontrol, including autism spectrum disorders (ASD). To date, no studies have reported on the effectiveness of RO DBT for people with ASD. Forty-eight patients were referred to a RO DBT programme, of whom 23 had a diagnosis of ASD. Outcome was measured using the Clinical Outcomes in Routine Evaluation – Outcome Measure (CORE) and the Questionnaire about the Process of Recovery. Results: The intervention was effective, with a medium effect size of 0.53 for improvement in CORE global distress. End-point CORE global distress score was predicted from initial severity and a diagnosis of ASD. Participants with a diagnosis of ASD who completed the therapy had significantly better outcomes than completing participants without an ASD diagnosis. Clinical implications: These findings provide preliminary support for RO DBT as an effective intervention for ASD in routine settings.